Estimation of temperature during TIG welding of titanium. Issue 1 (July 2021) - Raja, Avinash Ravi; Dixit, Anuj; Jain, Ayush; Husain, Syed Qaisar; Varshney, Gagan; Singh, Sudesh
Abstract: In this experimentation work, the welding of titanium (commercially pure of grade 2) has been performed. The technique used to perform the welding is Tungsten Inert Gas Welding. Several experimentations have been performed to get the preferred welding. On which further studies have been done. Temperature has been measured during the welding process to get the estimation.